Thinking Critically About Classifying Adverse Events: Incidence of Pancreatitis in Patients Treated With Nivolumab + Ipilimumab - Friedman, Claire F; Clark, Varina; Raikhel, Andrew V; Barz, Tim; Shoushtari, Alexander N; Momtaz, Parisa; Callahan, Margaret K; Wolchok, Jedd D; Chapman, Paul B; Hellmann, Matthew D; Postow, Michael A (JNCI : Journal of the National Cancer Institute, 2017)
The Common Terminology Criteria for Adverse Events (CTCAE) were developed to document the adverse effects of chemotherapy but are now also used to document immune-related adverse events (irAE). Characterization of irAE by the CTCAE has implications for determining dose-limiting toxicity (DLT) and, consequently, the recommended phase II dose (RP2D) of investigational agents. In the phase I trial of nivolumab + ipilimumab, an asymptomatic increase in lipase was the primary DLT that informed the RP2D. We performed a retrospective study of 119 patients with melanoma who were treated at Memorial Sloan Kettering Cancer Center with the combination of nivolumab + ipilimumab to investigate the relationship between asymptomatic grade 3 or higher increases in amylase and/or lipase and pancreatitis, a known irAE. Of the 119 patients, there were only two cases of pancreatitis, representing 20% of patients with grade 3 or higher amylase, 6.3% of patients with grade 3 or higher lipase, and 20% of patients with grade 3 or higher elevations of both enzymes. The application of the CTCAE, especially in grading independent lab values, should be considered carefully in clinical trials of novel immunotherapeutic agents.